Awareness of consumer rights and involvement in the buying process of high school students - Sebastian, Sean B.; Gabriel, Florenda S. (2005.)
This research aimed to describe the level of awareness of consumer rights of high school students and their level of involvement in the buying process. It also determined the difference between the level of awareness and the students' year level and the relation between the level of awareness and the students' involvement in the buying process. One hundred first year and one hundred fourth year selected students selected through cluster sampling from Pasay City West High School participated in the study. A self-administered questionnaire was used to gather data. Independent sample T-test was used to analyze the gathered data to determine the difference between the level of awareness of consumer rights of students and the students' year level. Pearson correlation was used to determine the relation between the level of awareness and the student's involvement in the buying process. The results showed that there was a relatively low level of awareness of consumer rights among high school students. The consumer rights most students are aware of or can easily recall is the right to choose followed by the right ti information, and the last is the right to redress. None of the respondents could recall that they have the right to a healthy environment and more importantly the right for consumer education. There was a significant difference between the students' level of awareness and their year level. Furthermore, a significant relation was found only between the students' level of awareness and their involvement in family purchase. Overall, involvement in buying different kinds of goods does not ensure awareness of eight consumer rights.
Thesis (BSHE)--University of the Philippines Diliman
Keywords: Consumers -- Philippines; Teenagers as consumers